(untitled) (Caligrama: Revista de Estudos Românicos, 2012)
Resumen: En el marco de los esquemas de intransitividad y transitividad indirecta (preposicional), este trabajo se limita a describir algunos ejemplos de verbos que alternan entre una construcción pronominal y otra no pronominal en portugués al contrario del uso pronominal único que presentan en español. Este tipo de alternancia diatética arranca del empleo de la voz media que en latín asumía distintos valores o acepciones y que explica el hecho de que una buena parte de verbos transitivos se construyan necesariamente como pronominales cuando se emplean como intransitivos. Palabras clave: Intransitividad; transitividad indirecta; voz media; portugués; español. Abstract: Under the sign of intransitivity and indirect transitivity (prepositional) models, this paper purposes only to describe a few examples of verbs that transit from a pronominal construction to a non-pronominal one in Portuguese, in opposition to that exclusive pronominal type, as it occurs in Spanish. This kind of diatectic alternation derives from the use of the middle voice which, in Latin, assumed distinct values or meanings, what explains why a number of transitive verbs are necessarily constructed as pronominal ones when they are applied as intransitive verbs. Keywords: Intransitivity; indirect transitivity; middle voice; Portuguese; Spanish.